Surface modification of titanium and its alloys in orthopedic applications / Tan Ai Wen - Tan, Ai Wen (2015)
The clinical success of any orthopaedic implant is dependent upon the interaction between the implant surface and the respective bone tissue, termed osteo-integration. However, current orthopaedic implants are still limited in effectiveness by the lack of appropriate cell adhesion and osteo-integration due to the intervention of fibrous tissue, leading to implant dislocation, premature loosening and consequently a reduced implant lifespan. Titanium (Ti) and its alloys, which have favourable mechanical properties, superior corrosion resistance and excellent biocompatibility, have been widely investigated for use in orthopaedic implants, but yet fail to achieve exemplary clinical results due to poor osteo-integration. To address these limitations, we investigated and assessed the modification of Ti oxide surface structures by introducing nanotopographical features that mimic the physiological hierarchical nanostructures of natural bone tissue to impart enhanced osteo-integration. Titania (TiO2) nanofiber/nanowire arrays, fabricated by a simple thermal oxidation technique, provide an interface that is capable of promoting osteo-integration similar to native bone tissue. In this study, we focus on the fabrication of in situ titania nanofiber/nanowire arrays via a thermal oxidation technique, and the clinical feasibility of these nanostructured surfaces for various in vitro cellular behaviours. The outcomes of this work have been promising as these as-grown TiO2 nanofibrous/nanowire surface structures resulted in enhanced cellular response of osteoblast, chondrocytes, and adipose-derived stem cells (ADSCs). These evidences suggest an inexpensive and highly scalable means to fabricate TiO2 nanofiber/nanowire arrays and demonstrate their potential use as a beneficial interface for orthopaedic implants.